2006
DOI: 10.1007/s00520-006-0172-0
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the palliative care mobile team on symptom assessment and medication profiles in patients admitted to a comprehensive cancer center

Abstract: Palliative care mobile teams make multiple changes in previous medications and provide almost universal counseling services to patients and families. The length of involvement with the patient and family is short; therefore, rapid stabilization and counseling are required. Our findings regarding medication changes could be helpful to tertiary care hospitals and cancer centers considering palliative care consultation teams.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
26
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 20 publications
2
26
0
Order By: Relevance
“…[34][35][36][37][38][39][40][41] According to two analyses of patients with terminal cancer in varied palliative care settings, fatigue was the most frequently reported symptom, and pain, depression, and anxiety were the most distressing symptoms. 2,42 In this study, the most frequently reported symptoms were pain (58%), dyspnea (52%), constipation (45%), and fatigue (23%). The incidence of presented symptoms could be related to the cancer type and site of metastasis.…”
Section: Discussionmentioning
confidence: 56%
“…[34][35][36][37][38][39][40][41] According to two analyses of patients with terminal cancer in varied palliative care settings, fatigue was the most frequently reported symptom, and pain, depression, and anxiety were the most distressing symptoms. 2,42 In this study, the most frequently reported symptoms were pain (58%), dyspnea (52%), constipation (45%), and fatigue (23%). The incidence of presented symptoms could be related to the cancer type and site of metastasis.…”
Section: Discussionmentioning
confidence: 56%
“…Both the outpatient center and the inpatient services are capable of rapidly improving physical and emotional distress. 17,18 In a recent study, we found a significant reduction of pain, fatigue, nausea, drowsiness, dyspnea, anorexia, sleep depression, and anxiety among 406 outpatients at their follow-up visit. 3.…”
mentioning
confidence: 88%
“…Only 22 patients (25%) were able to complete both the baseline and follow-up ESAS. For the patients who did complete the ESAS, significant improvements were documented in pain ( Delirium improved in 21 patients (30%) who were able to complete the MDAS from an initial median score of 13 (range, 8-21) to a median MDAS score of 11 (range, [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. Of these 21 patients, 20 (95%) were discharged alive (9 patients were discharged to home with hospice services, 5 patients were discharged to an inpatient hospice unit, 4 patients were discharged to home with outpatient follow-up, and 2 patients were discharged to a skilled nursing facility).…”
Section: (26)mentioning
confidence: 99%
“…The palliative care team (PCT) consists of a palliative care physician, palliative care and oncology fellows, advance practice nurses, a social worker, a case manager, a child-life specialist, and a psychiatric nurse counselor. The PCT consults with patients in all areas of the institution about symptom control and palliative care issues through a consult team, 13 an outpatient palliative care clinic, and a 12-bed inpatient palliative care unit (PCU). 14 The consult team provides services to patients who are treated by our medical and surgical oncology departments and is staffed by palliative care physicians certified by the American Board of Hospice and Palliative Medicine, 1 full-time palliative care advanced practice nurse, and 1 palliative medicine fellow in training.…”
mentioning
confidence: 99%